Association between self-assessed preoperative level of physical activity and postoperative complications – An observational cohort analysis within a randomized controlled trial (PHYSSURG-C). Issue 4 (April 2022) - Onerup, Aron; Angenete, Eva; Bock, David; Haglind, Eva
Abstract: Introduction: Physical activity has been suggested as a modifiable risk factor for postoperative recovery after major surgery. We aimed to further define the association between self-reported leisure time physical activity and postoperative complications and recovery on a group level. Materials and methods: An observational cohort analysis was performed within a randomized controlled trial. Patients ≥20 years with colorectal cancer were eligible. Between January 2015 and May 2020, 761 participants were recruited. Leisure time physical activity was self-assessed on a four-grade scale. The primary outcome in this analysis was postoperative complications within 90 days, measured with the comprehensive complication index (CCI). Secondary outcomes were CCI for the index hospital stay, CCI 30 days postoperatively, specific types of complications, length of hospital stay, and self-assessed physical recovery. Analyses were adjusted for gender, age, study center, alcohol consumption, tumor stage, colon/rectal cancer, neoadjuvant therapy, and open or laparoscopic surgery. Results: Data on preoperative physical activity was available for 614 participants. Participants who reported some physical activity had on average a lower CCI 90 days postoperatively than sedentary participants (odds ratio 0.63, 95% CI 0.43–0.92). Similar patterns were shown for complications during hospital stay and within 30 days. There were trends towards lower risk for several types of complications, reoperations and length of hospital stay but the only difference shown was for respiratory insufficiency. Conclusion: Physically active participants experienced fewer postoperative complications, which suggests the information has a potential prognostic value. The work for increasing physical activity in the general population should continue. Highlights: Habitual physical activity associated with less complications after colorectal cancer surgery Small increase from sedentary behavior associated with largest reduction of complications No association with specific postoperative complications A physically active population would withstand surgery better